1979
DOI: 10.1007/bf01962818
|View full text |Cite
|
Sign up to set email alerts
|

The effect of BCG-vaccination on vaccinia virus infections in mice

Abstract: Pretreatment with BCG yielded a high degree of protection against experimental vaccinia virus infections in mice. Corynebacterium parvum and Aristolochia acid were less protective; other immunostimulants were ineffective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The first is that heterologous immunity can be demonstrated between mycobacteria and viruses. Earlier reports had indicated that BCG or M. tuberculosis infection provided resistance in mice to VV or ectromelia virus, but in those studies the virus challenge was early after immunization, when immune responses to the mycobacteria were likely ongoing (3,16,40,44,56). In this present report, mice were treated with antibiotics to clear residual mycobacteria to minimum levels, the immune system appeared at rest (Table 1; Fig.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…The first is that heterologous immunity can be demonstrated between mycobacteria and viruses. Earlier reports had indicated that BCG or M. tuberculosis infection provided resistance in mice to VV or ectromelia virus, but in those studies the virus challenge was early after immunization, when immune responses to the mycobacteria were likely ongoing (3,16,40,44,56). In this present report, mice were treated with antibiotics to clear residual mycobacteria to minimum levels, the immune system appeared at rest (Table 1; Fig.…”
Section: Discussionmentioning
confidence: 50%
“…This indicates that these BCG-immune hosts were in a resting immune state without an overt ongoing immune response. This distinguishes this study from previous reports on resistance of BCG-infected or M. tuberculosis-infected hosts to heterologous pathogens at 7 to 21 days after exposure to the mycobacteria (3,40,44,56).…”
Section: Status Of the Bcg-induced Resting Memory Statementioning
confidence: 62%
See 2 more Smart Citations
“…While the mechanisms underlying these apparent heterologous beneficial effects of BCG remain unclear, the findings are certainly biologically plausible. BCG infection of mice significantly increases resistance to subsequent infection with Listeria and poxvirus . Vaccination of human neonates with BCG has been shown to alter the quality and amplitude of immune responses to heterologous vaccines .…”
Section: Potential Paths Forwardmentioning
confidence: 99%